Scaling behaviour near jamming in random sequential adsorption - Purvis, B.; Reeve, L.; Wattis, Jonathan A.D.; Mao, Yong (American Physical Society, 2015)
For the random Sequential adsorption model, we introduce the ‘availability’ as a new variable corresponding to the number of available locations in which an adsorbate can be accommodated. We investigate the relation of the availability to the coverage of the adsorbent surface over time. Power law scaling between the two is obtained both through numerical simulations and analytical techniques for both one- and two- dimensional random sequential adsorption, as well as in the case of competitive random sequential adsorption in one dimension.